Peningkatan Pengetahuan kesehatan Reproduksi siswi di SMKN 24 Jakarta Timur - Ariestanti, Yenni; Sapta Yanuar, Ignatius Erik; Widayati, Titik; Aprilia, Anggi Rahma; Hendra, Hendra; Sanusi, Anisa; Putri, Nafszagyah Desma (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
Teenagers are one of the largest components in Indonesia. Therefore, teenagers must be able to achieve excellence in all fields to become a high-quality generation that will carry the nation forward. In order to become a high-quality generation, teenagers must be able to avoid and address complex teenage issues that arise during their transitional phase. These issues are related to reproductive health, including problems such as unwanted pregnancies (KTD) and abortions, sexually transmitted diseases (STDs), and substance abuse. Teenagers between the ages of 15-18 are at the highest risk of alcohol use, drug use, and sexual activity. The goal of improving healthy reproductive behavior in female students in the 10th and 11th grades at SMKN 24 Jakarta involves four methods: activity planning, activity implementation, group education for teenagers, and activity monitoring, with knowledge levels measured through pre-tests and post-tests. The results show that educational activities and knowledge improvement have been successfully carried out with the participation of 100 female students in the 10th and 12th grades on August 22, 2023, at SMKN 24. The students received information on the growth and development of reproductive organs in teenagers, the importance of maintaining healthy reproductive organs to prevent sexually transmitted diseases and early pregnancies, and the readiness of female teenagers from physical, mental, and social aspects. Group education was provided for both teenagers and teachers. The analysis results indicate a 79% increase in knowledge, as tested using statistical analysis with a significance level of 0.000. This indicates that health education has a significant impact on improving the knowledge of female students. The PKM team also handed over equipment, such as a phantom model and reproductive health information sheets, to SMKN 24, which will be used in reproductive health education activities and promoting healthy behavior changes. Keywords: behavior, healthy reproduction, female students, SMKN 24